2009
DOI: 10.1111/j.1468-2370.2008.00238.x
|View full text |Cite
|
Sign up to set email alerts
|

Quality management, environmental management and firm performance: A review of empirical studies and issues of integration

Abstract: Quality management (QM) and environmental management (EM) are two business practices that may affect firm performance. These practices are being increasingly introduced into firms, which often use them jointly owing to their similarities. As a result of these similarities, their integration has become a popular topic of research and practice. In the field of integration, the highest level of integration may be achieved by means of a single, full QM-EM system (QEM) in which QM and EM lose their independence. It… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
128
1
16

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 154 publications
(155 citation statements)
references
References 114 publications
(110 reference statements)
1
128
1
16
Order By: Relevance
“…Regarding environmental performance, the impact of QM practices is significant on Resource consumption reduction but insignificant on Emission reduction. A possible explanation for insignificant influence of QM practices on Emission reduction might be that QM focuses on eliminating wastes of inefficient processes rather than reducing pollution in form of emissions [4]. Therefore, one suggestion to better address the environmental issues is to integrate QM with environmental management system, as exemplified by ISO 9001 and ISO 14001 integration [61].…”
Section: Findings and Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Regarding environmental performance, the impact of QM practices is significant on Resource consumption reduction but insignificant on Emission reduction. A possible explanation for insignificant influence of QM practices on Emission reduction might be that QM focuses on eliminating wastes of inefficient processes rather than reducing pollution in form of emissions [4]. Therefore, one suggestion to better address the environmental issues is to integrate QM with environmental management system, as exemplified by ISO 9001 and ISO 14001 integration [61].…”
Section: Findings and Discussionmentioning
confidence: 99%
“…Some studied examined QM and antecedent of economic performance such as operational performance [12,28,38,39,[51][52][53][54], production performance [34], and quality performance [22,23,26,33,55,56]. Regarding environmental performance, some studies found the contribution of quality management system to environmental performance [4,[57][58][59][60]. Empirical evidence shows that enterprises with QM implementation in accordance with ISO 9001 intertwine with environmental management system ISO 14001 obtain higher benefits than the others [61].…”
Section: Research On Quality Management and Sustainability Performancementioning
confidence: 99%
See 3 more Smart Citations